Pengaruh Diameter Pelat Helical Terhadap Kapasitas Daya Dukung Lateral Pondasi Helical Pada Tanah Gambut - Suryadi Ramadhan; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Application of helical pile to support structures constructed on peat is still a new method. Research is needed to discover ability of helical fondation replace wood pile. There were 6 different helical piles, wood pile, and plain pile embedded in peat. This research aimed to determined the behavior from effect of diameter variations helical plate to lateral bearing capacity of helical pile on peat soil. The distribution process lateraly load based on constant rate of penetration procedure with eccentricity 500 mm and 300 mm. The calculation of lateral bearing capacity theoretically using the method of Brinch Hansen (1961) and Methods Broms (1964). Interpretation method used are standard lateral failure structure. The addition diameter helical plate will Improved lateral bearing an average of 25 N. Reduction of the eccentricity value by 20 cm will increased the lateral bearing capacity average of 39 N. The results of trial and error in determined the cu correlation value is 0.05cu.Keywords: Helical Pile, Plate Diameter, Peat, Lateral bearing Capacity, Eccentricity, Wood Pile.